قرآن کریم کی سائنسی تفسیر اورعصر حاضر میں مفسرین کی ذمہ داریاں: Quranic scientific Commentary and Responsibilities of commentators in modern Era - Saddaqat Hussain; Dr. Amjad Hayat (MEI, 2022)
Everything is contained in Allah's Book. The Qur'an contains information on the history and issues surrounding many different scientific fields. It describes strange creatures and things found in the heavens, earth, horizon, high and underground, as well as the origin of creation, the names of famous prophets and angels, and previous nations' events. The concepts of the Qur'an have been unchallenged by science up until this point. Islam and the Quran have elevated science in society. I It doesn't seem to be true that Islam was the first faith to endorse science. Islam's observant and enquiring spirit has inspired people around the world to place a higher value on education and study. The purpose of scientific commentary is to help people understand the Quran, not to advance science. There is a scientific aspect to it as well. This will allow scientists to explore new realms of knowledge and research. These sophisticated individuals seek a logical, empirical understanding of the Quran's relevance and truth. It is raised whether scientific commentary is useful now and what impact it will have on society. The next generation, enmeshed in the tangle of human and modern issues and influenced by secular notions, refined the solution in Scientific Commentary. These well-educated moderns seek advice after being influenced and impressed by Scientific Commentary. As a result, the Scientific Commentary has been embraced by numerous Islamic interpreters, with favorable results.